Three-dimensional printing of metals for biomedical applications - Ni, J. (Mater Today Bio, 2019)
Three-dimensional (3D) printing technology has received great attention in the past decades in both academia and industry because of its advantages such as customized fabrication, low manufacturing cost, unprecedented capability for complex geometry, and short fabrication period. 3D printing of metals with controllable structures represents a state-of-the-art technology that enables the development of metallic implants for biomedical applications. This review discusses currently existing 3D printing techniques and their applications in developing metallic medical implants and devices. Perspective about the current challenges and future directions for development of this technology is also presented.